Effectiveness of Distribution Smart Buleleng Program at BAZNAS Buleleng Regency - Nur Aswani; Masyhuri Mahfudz; harisatunniswa_ (Ahwal Al-Syakhsiyyah Fakultas Syariah - Universitas Al-Qolam Malang, 2023)
This research is intended to understand and describe the distribution of Buleleng Cerdas program with a qualitative approach and case study research type. Data collection was carried out using observation, interview, and documentation techniques. The results of this research show that the distribution of the Buleleng Cerdas program at BAZNAS Buleleng Regency is intended for underprivileged Muslim students to help improve the quality of mustahik, ease the burden on parents regarding the financing contained in the world of education. The distribution of the Buleleng Cerdas Program is carried out through submissions from educational institutions/individuals to BAZNAS. The submission is then verified by the BAZNAS team and then the determination of potential beneficiaries is channeled through the bank or institution concerned. The condition of the effectiveness of the distribution of the Buleleng Cerdas program in an effort to improve the quality of mustahik in BAZNAS Buleleng Regency is effective, this can be seen from the measurement of the ACR (Allocation to Collection Ratio) of BAZNAS Buleleng Regency which obtained a value of> 90 with a very effective category 3 times in 2016, 2017 and 2019. ABSTRAK Penelitian ini dimaksudkan untuk memahami serta mendeskripsikan penyaluran program Buleleng Cerdas dengan pendekatan kualitatif dan jenis penelitian studi kasus. Pengumpulan data dilaksanakan dengan teknik observasi, wawancara, serta dokumentasi. Hasil penelitin ini menunjukkan bahwa penyaluran program Buleleng Cerdas di BAZNAS Kabupaten Buleleng diperuntukkan kepada pelajar muslim yang kurang mampu untuk membantu meningkatkan kualitas mustahik, meringankan beban orang tua mengenai pembiayaan yang terdapat dalam dunia pendidikan. Penyaluran Program Buleleng Cerdas dilaksanakan melalui pengajuan dari lembaga pendidikan/ perorangan kepada BAZNAS. Pengajuan tersebut selanjutnya diadakan verifikasi oleh tim BAZNAS kemudian penentuan calon penerima bantuan yang disalurkan melalui Bank atau lembaga yang bersangkutan. Kondisi efektivitas penyaluran program Buleleng Cerdas dalam upaya peningkatan kualitas mustahik di BAZNAS Kabupaten Buleleng sudah efektif hal tersebut dapat dilihat dari pengukuran ACR (Allocation to Collection Ratio) BAZNAS Kabupaten Buleleng yang memperoleh nilai >90 dengan kategori sangat efektif sebanyak 3 kali pada tahun 2016, 2017, dan 2019.